2003
DOI: 10.1038/sj.cdd.4401237
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for the nuclear localization of FADD

Abstract: The Fas-associated death domain (FADD) adaptor protein FADD/Mort-1 is recruited by several members of the tumor necrosis factor receptor (TNFR) superfamily during cell death activated via death receptors. Since most studies have focused on the interaction of FADD with plasma membrane proteins, FADD's subcellular location is thought to be confined to the cytoplasm. In this report, we show for the first time that FADD is present in both the cytoplasm and the nucleus of cells, and that its nuclear localization re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 31 publications
7
87
0
1
Order By: Relevance
“…We found that the adaptor molecule, FADD, was also present in fetal MSC, and that its expression was both cytosolic and nuclear ( Figure 2b). The nuclear localisation of FADD is consistent with a recent report 13 and might explain the interaction of FADD with several nuclear proteins involved in apoptosis, including methyl-Cpg binding protein-4. 14 Caspase 8 was also found to be expressed in human fetal MSC (not shown).…”
supporting
confidence: 91%
“…We found that the adaptor molecule, FADD, was also present in fetal MSC, and that its expression was both cytosolic and nuclear ( Figure 2b). The nuclear localisation of FADD is consistent with a recent report 13 and might explain the interaction of FADD with several nuclear proteins involved in apoptosis, including methyl-Cpg binding protein-4. 14 Caspase 8 was also found to be expressed in human fetal MSC (not shown).…”
supporting
confidence: 91%
“…The wild type and FADD-deficient MEFs were equally sensitive to nuclear TRADD-induced death indicating that FADD was not required for activation of the apoptotic pathway by nuclear TRADD (Figure 1c). Although FADD can be localized to the nucleus, 19,20 the nuclear TRADD construct consists of only amino acids 222-289, which is smaller than the region of the protein (aa 195-312) that was previously reported to be required for FADD-TRADD interaction. 21 We therefore tested if nuclear TRADD could interact with FADD in a directed two hybrid.…”
Section: Nuclear Tradd-induced Death Is Caspase-8 and Fadd-independentmentioning
confidence: 94%
“…33 In contrast, it has been documented that overexpressed FADD causes the formation of filamentous structures in the nucleus and cytoplasm. 34 More recently it has been reported 35,36 that the primary localisation of FADD is in the nucleus of adherent cells, whereas in nonadherent cells, such as Jurkat T cells, nuclear localisation of FADD was observed in 50% of cells and cytoplasmic localisation in the remainder. Subcellular fractionation and confocal microscopy experiments were used to determine the localisation of endogenous FADD in adherent and nonadherent cells of mouse and human origin.…”
Section: Subcellular Localisation Of Faddmentioning
confidence: 99%
“…34 This discrepancy may be due to the use of overexpression systems, which can cause artefacts in subcellular protein localisation. Moreover, recent studies with adherent cells 35,36 indicated that the primary localisation of endogenous FADD was inside the nucleus. The authors used a commercial anti-human FADD mAb.…”
Section: Fadd and Caspase-8 Do Not Localise In Membrane Raftsmentioning
confidence: 99%